2021
DOI: 10.1002/1873-3468.14204
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of desmosome function leads to increased centrosome clustering in 14‐3‐3γ‐knockout cells with supernumerary centrosomes

Abstract: 14‐3‐3 proteins are conserved, dimeric, acidic proteins that regulate multiple cellular pathways. Loss of either 14‐3‐3ε or 14‐3‐3γ leads to centrosome amplification. However, we find that while the knockout of 14‐3‐3ε leads to multipolar mitoses, the knockout of 14‐3‐3γ results in centrosome clustering and pseudo‐bipolar mitoses. 14‐3‐3γ knockouts demonstrate compromised desmosome function and a decrease in keratin levels, leading to decreased cell stiffness and an increase in centrosome clustering. Restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 94 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…In glioblastoma, silencing YWHAG inhibited migration and invasion 38 . The knockdown of YWHAG led to centrosome clustering and further regulated the cell cycle 39 . It has been reported that YWHAG could bind to Rac1, which has been shown to associate with the cytoskeleton and regulate cytoskeleton remodeling and cell migration 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In glioblastoma, silencing YWHAG inhibited migration and invasion 38 . The knockdown of YWHAG led to centrosome clustering and further regulated the cell cycle 39 . It has been reported that YWHAG could bind to Rac1, which has been shown to associate with the cytoskeleton and regulate cytoskeleton remodeling and cell migration 40 .…”
Section: Discussionmentioning
confidence: 99%